2014
DOI: 10.1136/bmjdrc-2014-000039
|View full text |Cite
|
Sign up to set email alerts
|

Age at diagnosis predicts deterioration in glycaemic control among children and adolescents with type 1 diabetes

Abstract: BackgroundPoor glycemic control early in the course of type 1 diabetes mellitus (T1DM) increases the risk for microvascular complications. However, predictors of deteriorating control after diagnosis have not been described, making it difficult to identify high-risk patients and proactively provide aggressive interventions.ObjectiveWe examined whether diagnostic age, gender, and race were associated with deteriorating glycemic control during the first 5 years after diagnosis.Participants2218 pediatric patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 38 publications
8
54
2
Order By: Relevance
“…The patients with high HbA1c at diagnosis continued to have poor metabolic control as a group. This is in line with a study by Clements et al, where older age at diagnosis was a predictor for deterioration in glycemic control during the first five years after diagnosis, and they also presented with higher HbA1c values . This could be due to hormone‐ induced insulin resistance during puberty .…”
Section: Discussionsupporting
confidence: 91%
“…The patients with high HbA1c at diagnosis continued to have poor metabolic control as a group. This is in line with a study by Clements et al, where older age at diagnosis was a predictor for deterioration in glycemic control during the first five years after diagnosis, and they also presented with higher HbA1c values . This could be due to hormone‐ induced insulin resistance during puberty .…”
Section: Discussionsupporting
confidence: 91%
“…Crucially, previous reports [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have largely examined individuals with pre-existing type 1 diabetes (i.e. not from the time of diagnosis).…”
Section: Introductionmentioning
confidence: 99%
“…The DCCT has unequivocally shown that intensive insulin therapy reduces risk of long‐term vascular complications, largely through improved HbA1c levels, and that better metabolic control in the early years of diabetes is also important in reducing this risk . Metabolic control commonly deteriorates during adolescence in many, but not all, patients with T1D . This may be due to physiological and to psychosocial influences, leading to insulin resistance, poor treatment adherence, eating disorders, and depression .…”
Section: Sub‐optimal Metabolic Controlmentioning
confidence: 99%
“…This may be due to physiological and to psychosocial influences, leading to insulin resistance, poor treatment adherence, eating disorders, and depression . Certain demographic and socioeconomic factors are also associated with higher HbA1c . Metabolic control during adolescence appears to have a greater association of microvascular complication in later life when compared with subsequent metabolic control in adult years …”
Section: Sub‐optimal Metabolic Controlmentioning
confidence: 99%